Keeping Teachers Afloat with Instructional Coaching: Coaching Structure and Implementation - SIAW HUI KHO; Thapanee Khemanuwong; Shaik Abdul Malik Mohamed Ismail (My University, 2020)
Despite the press for instructional coaching as a form of effective teacher professional development (TPD), there is still a need to understand what instructional coaching is and how its operations look like. Meanwhile, the coaching literature provides scant guidance particularly about the coaching implementation in the Malaysian context. For the purpose of this study, we explored the processes of instructional coaching in Sarawak, particularly focusing on conceptualising the coaching processes to fine-tune teaching practice. Employing a qualitative case study design, we conducted non-participant observations on coaching conferences of four coach-teacher pairs on a one-to-one basis. We analysed the data obtained using Braun and Clarke’s (2006) six-phase thematic analysis. The findings suggested that the coaching cycle consisted of three stages: pre-observation conference, classroom observation and post-observation conference. An additional stage of intervention was identified in the coaching cycle. Coaching support to the teachers was provided on an average of one session per month. Structuring coaching conversations was a key aspect in conducting coaching support for the teachers. For future research, we offer recommendations of larger-scale studies to discover the impact of instructional coaches that include the intervention component as a part of the coaching cycle to enhance teacher instruction and student achievement. We would also suggest studies based on comprehensive theories and empirical evidences into the development of fully articulated models of instructional coaching related to the Malaysian context.
Keywords: Thematic Analysis; Teacher Education and Leadership Studies